Efektifitas Penggembalaan di Gereja Bethel Indonesia Artaloka Tanggerang - Elisabeth Martumbur Manik (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
This article discusses the effectiveness of pastoral care at the Bethel Indonesia Artaloka Church which is located in Tanggerang, Banten. The dynamics of pastoral care cause a pastor to need various strategies and methods to increase the effectiveness of pastoral services to the congregation. By using a qualitative research approach and descriptive analysis methods, the data is then collected through observation and interviews and then the data is analyzed using descriptive analysis and presented comprehensively. The result obtained is that a pastor must be ready to give himself to the congregation, diligently working for the progress or improvement of the congregation, not for himself. To serve means to serve, to provide service in one's shepherding with a servant's heart. The effectiveness of the pastoral service at GBI Arthaloka is needed to continue to encourage or increase the congregation's motivation to attend existing services.